A robust single-antenna GNSS/MEMS fusion structure for reliable attitude determination in challenged environments - Jiaji Wu; Yuying Li; Tianci Tang; Wei Ding; Xiaoliang Meng; Jianghua Liu; Jinguang Jiang (Scientific Reports)
Abstract This study proposes an innovative single-antenna GNSS/MEMS integrated attitude determination system designed to address the challenges of low accuracy and poor robustness in urban complex environments, where conventional multi-antenna GNSS systems and standalone MEMS sensors often fail due to signal obstructions and drift errors. The key innovations include: (1) a hybrid TDCP/TDPR (Time Difference Carrier Phase/Pseudo-Range) technique to enhance GNSS-derived pitch and heading estimation, significantly improving data utilization; (2) a multi-strategy quality control framework incorporating Zero Velocity Detection (ZVD), Magnetic Disturbance Detection (MDD), and Fault Detection and Exclusion (FDE) to suppress outlier contamination and ensure measurement reliability; and (3) an adaptive noise parameter tuning mechanism to optimize filter performance. Experimental results demonstrate that the proposed system outperforms conventional SPP/MEMS, standalone MEMS, and baseline GNSS/MEMS fusion methods, achieving CDF95 attitude errors of 1.2785° (roll), 0.9412° (pitch), and 1.1991° (yaw)—the highest accuracy and robustness reported for single-antenna GNSS/MEMS systems in urban scenarios.